De Miranda do Douro ao Sabugal - arquitectura militar e testumunhos arqueológicos medievais num espaço de fronteira - Barroca, Mário Jorge (Portvgalia : Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da FLUP, 2018)
The author analyses the medieval evolution of a vast area in the east frontier of Portugal, between Miranda do Douro and Sabugal, from the Early Middle Age to the beginning of the 16th century. Although the main attention is centered in the evolution of military structures, other testimonies of the medieval occupation are also mentioned in this paper.